The Role of E-Commerce and Social Sustainability in Solar Renewable Green Energy (International Journal of Food and Nutritional Sciences, 2022)
Renewable sources has bright future as regular sources of energy diminishing year by year it is important to move towards the non-perishable source of energy. Now a days the solar energy becomes the widely used renewable source of energy as sun energy is available everywhere and use of solar energy does not cause harm to environment and human health. Government of India is supporting various scheme and policy to attract the entrepreneur to enter in renewable market. As renewable market is oligopoly market facing the tremendous competition. To attract the customer and to stand unique in this oligopolistic market various marketing strategy and business plan used by the organizations. By selling the product and services through online, vast consumer can be reached over short period of time which help to raise the turnover of organizations, so E-Commerce plays the vital role in solar business. To meet the increased requirements, opening employment from labour to high qualified people. Solar energy also helps to boost the economy. Solar energy directly and indirectly contributing to environment, society and economy. The aim is to understand the impact of E-Commerce and Social Sustainability in Solar Renewable Green Energy.